Eliminating Size-Associated Diffusion Constraints for Rapid On-Surface Bioassays with Nanoparticle Probes - Li, Junwei (Small, 2016)
Nanoparticle probes enable implementation of advanced on-surface assay formats, but impose often underappreciated size-associated constraints, in particular on assay kinetics and sensitivity. Here, we highlight substantially slower diffusion-limited assay kinetics due to the rapid development of a nanoprobe depletion layer next to the surface, which static incubation and mixing of bulk solution employed in conventional assay setups often fail to disrupt. In contrast, cyclic solution draining and replenishing (CDR) yields reaction-limited assay kinetics irrespective of the probe size. Using common surface bioassays, ELISA and immunofluorescence, we show that this conceptually distinct approach effectively “erases” size-dependent diffusion constraints, providing a straightforward route to rapid on-surface bioassays employing bulky probes and procedures involving multiple labeling cycles, such as multi-cycle single-cell molecular profiling. For proof-of-concept, we demonstrate that the assay time can be shortened from hours to minutes with the same probe concentration and, at a typical incubation time, comparable target labeling can be achieved with up to 8 times lower nanoprobe concentration. We expect our findings to enable realization of novel assay formats and stimulate development of rapid on-surface bioassays with nanoparticle probes.